Odpowiedź :
Odpowiedź:
8.:
3-1 i 1/8= 2 i 7/8 (pisz bez i)
3-2 i 1/6= 5/6
9.:
b) 7-4 i 2/9= 3-2/9= 2 i 7/9
c) 6- 3 i 1/11= 3-1/11= 2 i 10/11
d) 8-2 i 3/7= 6-3/7= 5 i 4/7
e) 6-1 i 5/9= 5- 5/9= 4 i 4/9
f) 10-5 i 4/11= 5 - 4/11= 4 i 7/11
Szczegółowe wyjaśnienie:
Mam nadzieję, że pomogłam.
Odpowiedź:
3 - 1 i 1/8 = 2 - 1/8 = 1 i 7/8
3 - 2 i 1/6 = 2 - 1/6 = 5/6
zad 9
6 - 1 i 2/5 = 5 - 2/5 = 4 i 3/5
7 - 4 i 2/9 = 3 - 2/9 = 2 i 7/9
6 - 3 i 1/11 = 3 - 1/11 = 2 i 10/11
8 - 2 i 3/7 = 6 -3/7 = 5 i 4/7
6 - 1 i 5/9 = 5 - 5/9 = 4 i 4/9
10 - 5 i 4/11 = 5 - 4/11 = 4 i 7/11